Ciliopathies and DNA damage: an emerging nexus. Issue 4 (July 2015) - Attanasio, Massimo
Abstract : Purpose of review: In the past decade a wealth of publications have established the central role of cilia and centrosomes in the pathogenesis of cystic kidney diseases, associated or not with extrarenal symptoms. This review outlines recent findings that have unexpectedly linked ciliary and centrosomal proteins to DNA damage and repair and have opened new perspectives for the comprehension of the pathogenesis of these diseases. Recent findings: Several ciliopathy proteins that contribute to the pathogenesis of cystic kidney diseases and ciliopathy-related phenotypes have been recently reported to participate in the elaborated pathways that control DNA replication and repair, suggesting that malfunction of these biological processes may be a common denominator of some ciliopathy-related diseases. Summary: In this review, the author briefly describes the established connections existing between cilia, centrosome, and cell cycle and provides basic information about DNA damage and repair. The author then examines more closely the single ciliopathy genes that have been associated with DNA repair pathways and their known biological functions.